REFORMULASI PENGATURAN KEWENANGAN BADAN INTELIJEN NEGARA DALAM HUKUM KEAMANAN NASIONAL BERDASARKAN KONSTITUSI RI - Abdas Raga Sugara; M. Hadin Muhjad; Rudi Indrawan (Al-Adl : Jurnal Hukum, 2026)
This study examines the regulation of the authority of the State Intelligence Agency (Badan Intelijen Negara/BIN) within the framework of national security law based on the Constitution of the Republic of Indonesia. The analysis focuses on three principal issues: (1) the regulation of BIN’s authority in national security law under the 1945 Constitution; (2) the nature of intelligence institutions within the national legal system; and (3) the reformulation of the scope of BIN’s authority in the Constitution and its implementing regulations. The research employs a normative juridical method with historical, conceptual, statutory, comparative, philosophical, and case-based approaches. The findings reveal the existence of legal residue and sociological problems following the enactment of Law Number 17 of 2011 on State Intelligence, particularly concerning democratic guarantees, the protection of human rights, accountability, and the political neutrality of intelligence activities. In addition, the absence of clear regulation regarding an Intelligence Committee has resulted in weak coordination and oversight of state intelligence. Accordingly, this study proposes a model for reconstructing BIN’s authority through the clarification of limits on interception and financial flow examinations based on judicial authorization, the establishment of an Intelligence Committee as an independent coordination and oversight mechanism, and the strengthening of the principles of accountability and political neutrality of intelligence within the framework of a democratic rule-of-law state.